Sutureless Abdominal Closure in Monozygotic Twin With Gastroschisis: A Case Report From Muhimbili National Hospital, Tanzania - Rajabu Athumani Bakari; Alfred Chibwae; Rajab Siaba Msemo; William W. Kahabi; Caroline S. Kanuti; Salma J. Ali; Godfrey Sama Philipo; Zaitun M. Bokhary; Judith Lindert; Kokila Lakhoo (Clinical Case Reports)
ABSTRACT Twin gastroschisis pregnancies poses challenges in prenatal diagnosis especially for multiple pregnancies among radiologists, and therefore impacts postnatal care by neonatologists and pediatric surgeons. This case emphasizes the successful management of twin babies born with gastroschisis, highligting the role of sutureless abdominal closure to the survival of twin babies.